The impact of diabetes-related complications on healthcare costs: new results from the UKPDS (UKPDS 84). - Alva, M; Gray, A; Mihaylova, B; Leal, J; Holman, R (2014)
AIMS: To estimate the immediate and long-term inpatient and non-inpatient costs for Type 2 diabetes-related complications. METHODS: The costs of all consultations, visits, admissions and procedures associated with diabetes-related complications during UK Prospective Diabetes Study post-trial monitoring in the period 1997-2007 were estimated using hospitalization records for 2791 patients in England and resource use questionnaires were administered to 3589 patients across the UK. RESULTS: The estimated (95% CI) inpatient care costs (in 2012 pounds sterling) in the event year for the example of a 60-year-old man were: non-fatal ischaemic heart disease £9,767 (£7,038-£12,696); amputation £9,546 (£6,416-£13,463); non-fatal stroke £6,805 (£3,856-£10,278); non-fatal myocardial infarction £6,379 (£4,290-£8,339); fatal stroke £3,954 (£2,012-£6,428); fatal ischaemic heart disease £3,766 (£746-£5,512); heart failure £3,191 (£1,678-4,903); fatal myocardial infarction £1,521 (£647-£2,670); and blindness in one eye £1,355 (£415-£2,655). In subsequent years, estimated (95% CI) costs ranged from £1,792 (£1,060-£2,943) for amputations to £453 (£315-£691) for blindness in one eye. Costs of non-inpatient healthcare in the event year were: amputation £2,699 (£1,409-£4,126); blindness in one eye £1,790 (£878-£3,056); non-fatal stroke £1,019 (£770-£1,499); nonfatal myocardial infarction £1,963 (£794-£1,157); heart failure £979 (£708-£1,344); non-fatal ischaemic heart disease £864 (£718-£1,014); and cataract extraction £700 (£619-£780). In each subsequent year, non-inpatient costs ranged from £1,611 (£1,193-£2,116) for amputations to £654 (£572-£799) for ischaemic heart disease. CONCLUSIONS: Diabetic complications are associated with substantial immediate and long-term healthcare costs. Our comprehensive new estimates of these costs, derived from detailed recent UK Prospective Diabetes Study post-trial data, should aid researchers and health policy analyses. This article is protected by copyright. All rights reserved.